(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to identify the "effect of the REAP strategy in developing the directing skills of the students of the Institute of Fine Arts" by verifying the hypothesis: "There are no statistically significant differences at the level (0.05) between the mean scores of the students of the experimental group who studied theatrical directing subject according to the strategy REAP and the mean scores of the students of the control group who studied the subject according to the usual method in the achievement test. It was distributed equally (15) male and female students into two groups, one the control and the other experimental, the two research groups were rewarded in the variables (chronological age, intelligence, previous information). The researchers prepared an achievement test consisting of (30) items, and its validity and reliability were verified after application. The results were treated statistically using (SPSS), as it showed the superiority of the students of the experimental group over the students of the control group in the achievement test variable. REAP" in teaching "Theatrical Direction" and suggested conducting other studies in other subjects and academic stages to identify its impact on different variables.